2017
DOI: 10.12991/mpj.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure-activity relationship study: Anticancer chalcones derived from 4'-morpholinoacetophenone

Abstract: The aim of this research was to synthesize chalcone derivatives containing morpholine ring and to investigate their antiproliferative activity. The 3-aryl-1-[4-(morpholin-4-yl)phenyl]prop-2-en-1-one derivatives were synthesized and evaluated for their in vitro antiproliferative activities on C6 cells (Rat glioma cell line) and HeLa cells (Human cervix adenocarcinoma), using the BrdU ELISA assay. The calculation of ADME properties of new chalcone derivatives was used by topological polar surface area (TPSA), ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Many studies for the design of ChEIs have shown that the nitrogen atom is essential for enzyme inhibitions, and the heterocyclic ring‐bearing chalcones containing a nitrogen atom are also necessary for other pharmacological activities 75–79 . Based on these findings, 20 chalcone derivatives have been designed in this study in the search for finding new potent and multi‐targeted inhibitors as drug candidates for the treatment of neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies for the design of ChEIs have shown that the nitrogen atom is essential for enzyme inhibitions, and the heterocyclic ring‐bearing chalcones containing a nitrogen atom are also necessary for other pharmacological activities 75–79 . Based on these findings, 20 chalcone derivatives have been designed in this study in the search for finding new potent and multi‐targeted inhibitors as drug candidates for the treatment of neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Chalcones containing the nitrogenous heterocyclic ring moiety attached to the phenyl ring at the para position were synthesized as outlined in Scheme 1. According to the Claisen–Schmidt condensation reaction, appropriate 4‐substituted benzaldehydes ( 1–5 ) were reacted with various aromatic/heteroaromatic methyl ketones ( a–d ) in the presence of NaOH in ethanol at room temperature to form the target chalcones (1a–d , 2a–d , 3a–d , 4a–d , and 5a–d) in yields ranging from 52% to 94% 54,79 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It forms a benzylidene acetophenone scaffold in which two aromatic structures are linked by a threecarbon α,β unsaturated carbonyl bridge. 9 It and its derivatives can be classically synthesized by the Claisen-Schmidt reaction 10 , as well as by the solid phase Claisen-Schmidt reaction 11 , can also be synthesized by various methods such as the solvent-free Claisen-Schmidt reaction 12 , the Suzuki Miyaura reaction 13 , the coupling reaction 14 , the carbonylative Heck coupling reaction 15 , the one-pot reaction of chalcones 16 , microwave method 17 , solid acid catalyst 18 , the Sonogashira isomerization connection 19 , Friedel Crafts reaction 20 , Juliae Kocienski Olefination. 21 Chalcones have various pharmacological activities such as anti-platelet 22 , antidiabetic 23 , antineoplastic 24 , antiangiogenic 25 , antiretroviral 26 , antiinflammatory 27 , antigout 28 , antihistaminic 29 , antioxidant 30 , antiobesity 31 , hypolipidemic 32 , antitubercular 33 , antifilarial 34 , antiinvasive 35 , antimalarial 36 , antiprotozoal 37 , antibacterial 38 , antifungal 39 , antiulcer 40 , antisteroidal 41 , immunosuppressant 42 , hypnotic 43 , anxiolytic 44 , antispasmodic 45 , antinociceptive 46 , and osteogenic.…”
Section: Introductionmentioning
confidence: 99%
“…Bu bilgiler ışığında, bu çalışmada SARS-CoV-2'nin replikasyonda önemli role sahip olan M pro enzimi ile 32 adet kalkon türevi bileşiklerin in siliko moleküler modelleme yöntemleri ile farmakokinetik ve farmakodinamik açıdan incelenmiştir. Analizi yapılan bu bileşiklerden 1-14 bileşikleri [23], 15-21 bileşikleri [24], 23 [25], 22, 24-26 bileşikleri [26], 27-32 bileşikleri [18] literatürlerinden alınmış olup Şekil 1'de yapıları belirtilmektedir.…”
Section: Introductionunclassified